THE INFLUENCE OF COMMUNITY PARTICIPATION ON THE EFFECTIVENESS OF COMMUNITY VILLAGE FUND MANAGEMENT WITH ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT AS AN INTERVENING VARIABLE (IN SIHOLI VILLAGE, BORONADU DISTRICT): PENGARUH PARTISIPASI MASYARAKAT TERHADAP EFEKTIVITAS PENGELOLAAN DANA DESA MASYARAKAT DENGAN AKUNTABILITAS PENGELOLAAN DANA DESA SEBAGAI VARIABEL INTERVENING (DI DESA SIHOLI KECAMATAN BORONADU) - Giawa, Sukahati; Halawa, Harapan (LPPM UPMI, 2023)
The purpose of this study was to find out and prove community participation and accountability of village funds to influence the effectiveness of village fund management in Siholi village, Boronadu sub-district, South Nias district. In this study, the population is the village government, the village community, Boronadu sub-district and village consultative bodies. This study uses purposive sampling, the sample is selected based on considerations that have the objective of obtaining more representative data. Distributing the questionnaire to respondents is a way to collect data. The results of the study show that participating communities and accountability in managing village funds have quite an effect on the effectiveness of managing village funds. This shows that participation by the community and accountability for managing village funds is getting higher, the effectiveness of village fund management, Siholo village, Boronadu sub-district, is also getting better.